2016
DOI: 10.1002/gps.4628
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depressive symptoms among older patients with hypertension in rural China

Abstract: Objective The comorbidity of depression and hypertension (HTN) is common and complicates the management of both conditions. This study investigated the prevalence of depressive symptoms among older patients with HTN in rural China and explored the relationship between the two conditions. Methods The baseline data of older patients diagnosed with HTN included in the depression/HTN in Chinese Older Adults—Collaborations for Health Study were used for the analysis. The Chinese Older Adults—Collaborations for He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
(55 reference statements)
3
27
0
6
Order By: Relevance
“…The results of mediation analyses supported our hypothesis that HTN control was mediated partially by treatment adherence in patients with HTN. These findings are consistent with previous work …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of mediation analyses supported our hypothesis that HTN control was mediated partially by treatment adherence in patients with HTN. These findings are consistent with previous work …”
Section: Discussionsupporting
confidence: 94%
“…As well, HTN and its sequelae are risk factors for depression, complicating help‐seeking, diagnosis, treatment, and prognosis . We recently reported that 13% of rural Chinese primary care patients aged 60 or more with HTN had clinically significant depressive symptoms and that the presence of depressive symptoms was associated with poor BP control—70% of those with depressive symptoms had uncontrolled HTN compared with 21% of those without …”
Section: Introductionmentioning
confidence: 99%
“…A large population based study in rural China showed much lesser prevalence of depression than our study which may be due to ethnical differences. 12 A hypertensive clinic based cross sectional study conducted in South India showed a prevalence of depression as 25% among hypertensive subjects. 13 The prevalence in this study is less compared to the present study as the sample size was less and it was rather not a population based study.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Among those with chronic diseases, the prevalence of depressive symptoms was as high as about 13%. 4 Hypertension is one of the most common chronic diseases in China and is estimated to have impacted nearly 52% of Chinese over 65 years old. 5 Prospective studies and meta-analyses including one of our own have shown that hypertension is a risk factor for incident depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%